Parenting girls with Rett syndrome: An investigation on self‐perceived levels of stress. Issue 6 (23rd June 2020) - Pari, Elisa; Cozzi, Francesca; Rodocanachi Roidi, Marina Luisa; Grange, Francesca; Toshimori, Kumiko; Ripamonti, Enrico
Abstract: Background: Although lives of parents of girls with Rett syndrome (RTT) are centred on the process of care, in the current literature their perceived levels of stress have been rarely investigated. Methods: We analysed levels of stress in a sample of 79 fathers and mothers parenting girls with RTT, who were required to compile the Parenting Stress Index (PSI) questionnaire. Results: We found clinical levels of stress in about 39% of fathers, as compared with 44% of the mothers. Severity of RTT, but not other factors such as the genetic domain, presence of epilepsy or scoliosis, predicted Total Stress scores in both fathers' subsample and mothers' subsample. A cumulative effect of caring, that is association of higher levels of stress with longer process of care, did also emerge from estimation of smoothing splines. Conclusions: Fathers' resources should be taken more into account, especially in the rehabilitation and socialization process of adults with RTT.